Steel sheet and method for manufacturing same
By forming a polyolefin wax organic resin film with a specific melting point and particle size on the surface of the original steel plate, the problems of insufficient stamping forming and poor film removal in complex forming are solved, and excellent stamping forming and film removal are achieved. , suitable for automotive steel plates.
Patent Information
- Application Number
- CN202380028546.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-25
- Filing Date
- 2023-03-15
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-03-15
AI Technical Summary
The existing steel plates are not stamped and formed in complex forming, easily break or stick to the mold, and have poor film removal properties in the coating process, which affects productivity and quality.
It is formed on the surface of the steel plate original plate with an organic resin film containing polyolefin wax with a melting point of 120°C or above and 140°C or below. The standard deviation of the film adhesion amount distribution is controlled to be less than 0.9g/m2, and the roughness and film adhesion amount of the steel plate original plate are adjusted to optimize The proportion and particle size of the wax are used to improve stamping and defiling properties.
The friction coefficient between the steel plate and the mold is significantly reduced, and stamping forming properties are improved. Especially in complex forming and high-strength steel plates, it ensures small sliding resistance and prevents sticking of the mold, while obtaining good film removal and coating properties.
Smart Images

Figure CN119156281A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a steel sheet having excellent sliding properties during press forming and a method for producing the same, and more particularly to a steel sheet having a lubricating film having excellent formability even during severe drawing and a method for producing the same. Background Art
[0002] Cold-rolled steel sheets and hot-rolled steel sheets are widely used in a wide range of fields, centered around automobile body applications, and are used by stamping. In recent years, there has been a demand for integration of parts to omit processes and for improved design, and more complex forming is required.
[0003] When more complicated press forming is to be performed, there is a possibility that the steel sheet cannot withstand the forming and breaks, or that die sticking occurs during continuous press forming, which may have a serious adverse effect on the productivity of the automobile.
[0004] As a method for improving the stamping formability of cold-rolled steel sheets and hot-rolled steel sheets, surface treatment of the die can be cited. Although it is a widely used method, this method cannot adjust the die after the surface treatment is performed. In addition, there is also the problem of high cost. Therefore, it is strongly required to improve the stamping formability of the steel sheet itself.
[0005] As a method for improving the stamping formability without performing surface treatment on the mold, there is a method of using a high-viscosity lubricating oil. However, in this case, sometimes poor degreasing occurs after stamping, and the paintability may deteriorate.
[0006] Therefore, various lubricated surface treated steel sheets are being studied as a technology that enables press forming without using surface treatment of the die or high-viscosity lubricating oil.
[0007] Patent Document 1 describes a metal plate coated with a lubricating film in which a solid lubricant protrudes from the surface of a resin film by 0.01 to 1.5 μm.
[0008] Patent Document 2 describes a lubricated surface-treated metal product having excellent press formability and coated with a film having a thickness of 0.5 to 5 μm and obtained by adding a lubricant to a polyurethane resin.
[0009] Patent Document 3 describes a technique for forming an alkali-soluble organic film on a steel sheet by adding a lubricant to an epoxy resin.
[0010] Prior art literature
[0011] Patent Literature
[0012] Patent Document 1: Japanese Patent Application Laid-Open No. 10-52881
[0013] Patent Document 2: Japanese Patent Application Publication No. 2000-309747
[0014] Patent Document 3: Japanese Patent Application Publication No. 2000-167981 Summary of the invention
[0015] Problems to be solved by the invention
[0016] However, in the techniques disclosed in Patent Documents 1 to 3, although lubricity is exhibited due to the lubricating effect of the lubricant contained therein, the press formability is not necessarily sufficient in complex forming.
[0017] The present invention is completed in view of the above situation, and its purpose is to provide a steel plate that is difficult to stamp and is complex to form, which has low sliding resistance at the parts that are prone to cracking during stamping and has excellent stamping formability at the parts where the surface pressure is high and sticking is expected to occur.
[0018] Furthermore, when used as a steel sheet for automobiles, it is also necessary to have sufficient releasability in the alkaline degreasing step in the painting step. In such an application, a further object is to provide a steel sheet having good releasability.
[0019] Methods used to solve problems
[0020] In order to solve the above problems, the inventors have repeatedly conducted in-depth research. As a result, it was found that in order to dramatically improve the stamping formability, an organic resin film containing a polyolefin wax having a melting point of 120°C or more and 140°C or less and an average particle size of 3.0 μm or less is formed on the surface of the steel plate original plate, and the standard deviation σ of the film adhesion distribution per single side of the organic resin film is less than 0.9 g / m 2 The above-mentioned problem can be solved by controlling the surface roughness of the steel plate original plate and the distribution of the coating adhesion within a specific range. In addition, it was found that the stamping formability can be further improved by setting the coating adhesion, the arithmetic mean roughness Ra of the steel plate original plate, the average particle size of the wax and the proportion of the wax in the coating to an appropriate range.
[0021] The present invention has been accomplished based on the above findings, and the gist of the present invention is as follows.
[0022] It should be noted that the steel plate original plate refers to the steel plate from which the film is removed, which exists as a base of the film containing organic resin and wax. In addition, as the steel plate original plate, a cold-rolled steel plate or a hot-rolled steel plate can be used.
[0023] [1] A steel plate comprising a steel plate base and a coating formed on at least one side of the steel plate base, wherein the coating comprises an organic resin and a wax, the steel plate base has an arithmetic mean roughness Ra of 0.4 μm or more, the organic resin is at least any one of an acrylic resin, an epoxy resin, a urethane resin, a phenolic resin, a vinyl acetate resin, and a polyester resin, the wax is a polyolefin wax having a melting point of 120° C. or more and 140° C. or less and an average particle size of 3.0 μm or less, the proportion of the wax in the coating is 10% by mass or more, and the standard deviation σ of the distribution of the coating amount per single side of the coating is less than 0.9 g / m 2 .
[0024] [2] The steel sheet according to [1], wherein the coating weight W per single surface of the coating is 2.0 g / m 2 the following.
[0025] [3] The steel sheet according to [1] or [2], wherein the arithmetic mean roughness Ra of the steel sheet base is 0.4 μm or more and 2.5 μm or less.
[0026] [4] The steel sheet according to any one of [1] to [3], wherein the average particle size of the wax is 0.01 μm or more and 0.5 μm or less.
[0027] [5] The steel sheet according to any one of [1] to [4], wherein the ratio of the wax in the film is less than 50% by mass.
[0028] [6] The steel sheet according to any one of [2] to [5], wherein the coating weight W per single surface of the coating is 0.9 g / m 2 the following.
[0029] [7] The steel sheet according to any one of [1] to [6], wherein the organic resin is an alkali-soluble resin.
[0030] [8] A method for manufacturing a steel plate, which is the method for manufacturing a steel plate according to any one of [1] to [7], wherein a coating containing the organic resin described in any one of [1] to [7] and a wax is applied to at least one surface of a steel plate original plate and dried.
[0031] [9] The method for manufacturing a steel plate according to [8], wherein the viscosity of the coating material is 1.5 mPa·s or more and 8.0 mPa·s or less.
[0032]
[10] The method for manufacturing a steel plate according to [8] or [9], wherein the maximum reaching temperature of the steel plate original plate during the drying is 60° C. or higher and 140° C. or lower, and the drying time during the drying is 2 seconds or higher and 150 seconds or lower.
[0033] Effects of the Invention
[0034] According to the present invention, a steel sheet having a significantly reduced friction coefficient between the steel sheet and a die, etc. and excellent press formability can be obtained. Therefore, a steel sheet with low strength that is to be subjected to complex forming can stably have excellent press formability.
[0035] In addition, even a high-strength steel sheet with increased surface pressure during stamping can be obtained that has low sliding resistance at locations prone to cracking during stamping and excellent stamping formability at locations where the surface pressure is high and sticking is expected to occur.
[0036] In addition, a steel sheet having good releasability can be obtained.
[0037] In the above, high strength means that the assumed tensile strength (TS) is 440 MPa or more, and low strength means that the assumed TS is less than 440 MPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a diagram showing the distribution of the local coating amount when the difference in coating amount between the concave portion of the steel plate and the convex portion of the steel plate is different.
[0039] Figure 2 It is a graph showing the distribution of the local film deposition amount when the average film deposition amount is different.
[0040] Figure 3 This is a diagram showing the distribution of the local coating amount when the surface roughness of the steel plate original plate is different.
[0041] Figure 4 This is a schematic front view of a friction coefficient measuring device.
[0042] Figure 5 It is shown Figure 4 A schematic three-dimensional diagram of the shape and size of the bead. DETAILED DESCRIPTION
[0043] Hereinafter, embodiments of the present invention will be described.
[0044] The present invention is a steel plate comprising a steel plate original plate and a coating formed on at least one side of the steel plate original plate, characterized in that the coating comprises an organic resin and a wax, the arithmetic mean roughness Ra of the steel plate original plate is greater than 0.4 μm, the organic resin is at least any one of an acrylic resin, an epoxy resin, a urethane resin, a phenolic resin, a vinyl acetate resin, and a polyester resin, the wax is a polyolefin wax having a melting point of greater than 120°C and less than 140°C and an average particle size of less than 3.0 μm, and the proportion of the wax in the coating is greater than 10% by mass. Furthermore, it is characterized in that the standard deviation σ of the distribution of the coating adhesion amount on each side of the coating is less than 0.9 g / m 2 .
[0045] The wax used in the present invention is not limited as long as it is a polyolefin wax having a melting point of 120° C. to 140° C. and an average particle size of 3.0 μm or less.
[0046] Polyolefin wax is used as the wax because it has low surface energy and self-lubricating properties, thus providing good lubricity. In addition, polyolefin can be easily adjusted to have a melting point of 120° C. or higher and 140° C. or lower by controlling density and molecular weight.
[0047] When the melting point is above 120°C and below 140°C, in addition to the self-lubricating property of the polyolefin wax itself, the wax becomes semi-molten due to sliding during stamping, so that the lubricating film component mixed with the organic resin can cover the mold surface, and an excellent lubrication effect can be obtained by suppressing direct contact between the mold and the steel plate. When the melting point is lower than 120°C, the wax completely melts due to the frictional heat generated by sliding during stamping, and not only the sufficient lubrication effect of the wax itself cannot be obtained, but also the above-mentioned mold coating effect cannot be obtained. In addition, when the melting point is higher than 140°C, the wax does not melt during sliding, and a sufficient lubrication effect cannot be obtained, and a mold coating effect cannot be obtained.
[0048] It is believed that when the melting point of the wax is above 120°C and below 140°C, in the sliding state during stamping, the wax in the film effectively adheres to the mold and is not easy to fall off, and a high lubrication effect can be obtained. When the melting point of the wax is lower than 120°C, even if the film adheres to the mold, the adhesion is weak, and the film easily falls off during sliding. When the melting point of the wax is higher than 140°C, the film is difficult to adhere to the mold. In addition, the melting point of the wax is preferably above 125°C and below 135°C.
[0049] Here, the melting point of the wax refers to the melting temperature measured in accordance with JIS K 7121:1987 "Methods for determining transition temperatures of plastics".
[0050] When the average particle size of the wax is greater than 3.0 μm, it is difficult to mix with the organic resin during sliding, and the coating effect of the mold cannot be obtained, and sufficient lubricity cannot be obtained. The average particle size of the wax is preferably 1.5 μm or less. The average particle size of the wax is more preferably 0.5 μm or less, and even more preferably 0.3 μm or less.
[0051] The particle size of the wax is preferably 0.01 μm or more. When the average particle size of the wax is less than 0.01 μm, it is easy to dissolve in the lubricating oil during sliding, and sometimes cannot fully exert the lubricity improvement effect. Even in the coating for forming the film, it is easy to aggregate, so the coating stability is also low. The average particle size of the wax is more preferably 0.03 μm or more.
[0052] The above-mentioned average particle size refers to the median particle size of the volume average diameter, which is obtained by laser diffraction / scattering method. For example, it can be obtained by measuring the sample diluted with pure water using a laser diffraction / scattering particle size distribution measuring device Partica (registered trademark) LA-960V2 (manufactured by Horiba, Ltd.).
[0053] Among polyolefin waxes, polyethylene wax is preferably used because the best lubricating effect can be obtained when polyethylene wax is used.
[0054] The mass ratio of the wax in the film is set to 10% by mass or more. When the mass ratio of the wax in the film is less than 10% by mass, a sufficient lubricating effect cannot be obtained. If the mass ratio of the wax in the film is 15% by mass or more, a particularly good lubricating effect can be obtained. In addition, the mass ratio of the wax in the film is preferably less than 50% by mass. When the mass ratio of the wax in the film is 50% by mass or more, due to the deficiency of the base resin component, the wax is easy to fall off, the adhesion to the steel plate original plate is poor, and sometimes it cannot be stably present in the form of a film. In addition, when used as a steel plate for automobiles, sometimes sufficient degreasing cannot be obtained in the alkaline degreasing process in the coating process, and even when using an alkali-soluble organic resin, sometimes the film cannot be fully removed in the alkaline degreasing process and the film remains, which deteriorates the coating property. The mass ratio of the wax in the film is further preferably 30% by mass or less.
[0055] Here, the ratio of the wax in the film refers to the ratio of the mass of the solid content of the wax in the film to the total mass of the solid content of the organic resin in the film and the mass of the solid content of the wax in the film.
[0056] As a specific measurement method, for resin and wax, test pieces with known film adhesion amounts on steel plate original plates are prepared, infrared absorption spectra are measured using an FT-IR measuring device, and calibration curves of the adhesion amounts of resin and wax are prepared based on the peak intensities from each of the resin and wax. Next, the infrared absorption spectrum of the lubricating film-coated steel plate to be measured is measured, and the adhesion amounts of resin and wax are calculated based on the calibration curve, thereby determining the mass ratio of wax in the film.
[0057] In the present invention, the organic resin acts as a binder to hold the wax on the surface of the steel plate. The sliding effect brought by the mold coating of the mixture of wax and organic resin formed during sliding cannot be exerted due to the low affinity of inorganic binders with polyolefins. As the organic resin, at least any one of acrylic resin, epoxy resin, urethane resin, phenolic resin, vinyl acetate resin, and polyester resin can be used.
[0058] The acrylic resin used in the present invention refers to a polymer or copolymer composed of one or more selected from unsaturated monocarboxylic acids having one carboxyl group in the molecule such as acrylic acid and methacrylic acid, esters of the above unsaturated monocarboxylic acids and styrene, or their derivatives such as sodium salts, potassium salts, ammonium salts and amine salts.
[0059] In the case of an acrylic resin containing as a monomer a fatty acid having two or more carboxyl groups in the molecule, coating stability may be deteriorated. Therefore, in the present invention, an acrylic resin containing as a monomer a fatty acid having one carboxyl group in the molecule or a fatty acid ester thereof is used.
[0060] The epoxy resin is not particularly limited, and examples thereof include bisphenol A epoxy resin, bisphenol F epoxy resin, and novolac epoxy resin.
[0061] The urethane resin is not particularly limited, but preferably has a carboxyl group in the molecule.
[0062] The phenolic resin is not particularly limited, but a resol-based phenolic resin that can be dissolved or dispersed in an aqueous solvent is preferred.
[0063] The vinyl acetate resin is not particularly limited, but polyvinyl acetate is preferably used.
[0064] The polyester resin is not particularly limited, but is preferably a polyester resin containing a monomer having a carboxyl group as a constituent component.
[0065] Furthermore, these resins may be used in combination of two or more. In addition, by using an alkali-soluble organic resin, the film can be removed by alkaline degreasing in the coating process, and the subsequent coating properties become good.
[0066] In the present invention, as components other than the organic resin and the wax, a surface conditioner, a defoaming agent, and a dispersant may be contained. In addition, a rust preventive agent may be added to improve rust resistance.
[0067] In the present invention, when the above-mentioned film is formed on the surface of the steel plate original plate, the film with a wide range of adhesion amount is formed on the steel plate original plate with a wide range of surface roughness and the stamping formability is evaluated, and the state of the film is measured by SEM or EPMA equipped with an X-ray spectrometer. As a result, it was found that the standard deviation σ of the film adhesion amount distribution of the steel plate formed with the above-mentioned film was less than 0.9 g / m 2 The area stably satisfies good stamping formability.
[0068] Generally, the greater the surface roughness of the steel plate original plate, the thinner the film is likely to become at the convex parts of the steel plate original plate. During stamping, due to sliding with the die, the film is easily scraped off to expose the steel plate original plate as the base, making it difficult to obtain a lubricating effect.
[0069] However, by using the technology of the present invention, adhesion of the film component to the mold can be promoted during sliding, and even when the roughness of the steel plate original plate is large, the mold side can be protected, so lubricity is not impaired.
[0070] The film component that mainly contributes to the sliding property is the film component present on the convex part of the steel plate original plate that contacts the die during the stamping process. Generally, since the film coating is easily accumulated in the concave part of the steel plate original plate when the film coating is applied, the film adhesion amount on the convex part of the steel plate original plate and the concave part of the steel plate original plate is uneven, and there is a tendency that the film thickness on the convex part of the steel plate original plate becomes thinner and the film thickness on the concave part of the steel plate original plate becomes thicker.
[0071] Furthermore, depending on the coating properties such as the wettability of the coating, the coating conditions, the drying conditions, etc., the coating adhesion amount may be greater or less on the convex portion of the original steel plate even if the coating adhesion amount is the same.
[0072] Furthermore, the state of the coating amount on the convex parts of the original steel plate (hereinafter also referred to as convex parts) and the concave parts of the original steel plate (hereinafter also referred to as concave parts) also changes depending on the coating amount and the roughness of the original steel plate as the substrate.
[0073] like Figure 1 As shown in FIG. 1 , when the difference in the amount of film adhesion between the convex portion and the concave portion increases due to differences in certain coating properties, coating conditions, etc., the amount of film adhesion on the convex portion in contact with the die during stamping decreases, and the stamping formability decreases. At this time, the peak width representing the distribution of the amount of film adhesion of the entire film becomes wider, and the value of the standard deviation σ also becomes larger.
[0074] In addition, if Figure 2As shown in FIG. 1 , when the average film deposition amount changes, the peak representing the film deposition amount distribution of the entire film changes as shown below.
[0075] When the average coating amount is small, the stamping formability is reduced because the coating amount of the convex part cannot be sufficiently obtained. At this time, the peak position of the coating amount distribution of the convex part and the concave part shifts to the low adhesion side, and the peak interval between the convex part and the concave part widens. As a result, the peak width of the overall coating amount distribution widens, and the value of the standard deviation σ also increases.
[0076] On the other hand, when the average coating amount is high, the stamping formability is improved because the coating amount of the convex part can be sufficiently obtained. At this time, the peak positions of the coating amount distribution of the convex part and the concave part are shifted to the high adhesion side, and the peak interval between the convex part and the concave part is narrowed. As a result, the peak width of the overall coating amount distribution is narrowed, and the value of the standard deviation σ is also reduced.
[0077] In addition, if Figure 3 As shown in the figure, when the roughness of the steel plate original plate as the substrate changes, the peak width representing the overall coating adhesion amount also changes. When the roughness of the steel plate original plate is small, the uneven distribution of the coating adhesion amount of the convex and concave parts becomes smaller, and the coating adhesion amount of the convex part becomes stable, so the stamping formability is improved. At this time, the peak width of the coating adhesion amount distribution of the convex and concave parts becomes smaller, and the peak width of the overall coating adhesion amount distribution also becomes narrower. As a result, the value of the standard deviation σ also becomes smaller.
[0078] On the contrary, when the roughness of the steel plate original plate is large, the unevenness of the coating adhesion amount of the convex part becomes larger, so the stamping formability decreases. At this time, the peak width of the coating adhesion amount distribution of the convex part and the concave part becomes wider. Therefore, the peak width of the overall coating adhesion amount distribution also becomes wider, and the value of the standard deviation σ also becomes larger.
[0079] As described above, due to various reasons, the amount of film adhesion on the convex portion in contact with the die cannot be stably ensured, and the press formability is reduced.
[0080] When the film adhesion amount of the convex portion can be obtained stably and the stamping formability is good, the standard deviation σ of the film adhesion amount distribution of the entire film becomes smaller. When the film adhesion amount of the convex portion cannot be obtained stably and the stamping formability is poor, the standard deviation σ becomes larger.
[0081] Therefore, if the size of the standard deviation σ of the film adhesion amount distribution can be evaluated, it can be determined whether the stamping formability is good or not.
[0082] The standard deviation σ of the distribution of the coating adhesion amount can be evaluated as follows: the intensity diagram of the C-Kα ray, which is the main component of the coating, and the Fe-Kα ray, which is the main component of the base steel plate, are measured using a SEM equipped with an X-ray spectrometer, and the average value μ is calculated from the intensity ratio diagram thereof. C / Fe and standard deviation σ C / Fe to make an evaluation.
[0083] Since the average value μ C / Fe It is roughly proportional to the amount of film adhesion, so by comparing μ C / Fe The standard deviation σ of the C-Kα / Fe-Kα intensity ratio diagram can be calculated by comparing the amount of film adhesion to the C / Fe This was converted into the standard deviation σ of the distribution of the coating adhesion amount.
[0084] The calibration curve for converting the characteristic X-ray intensity ratio into the coating adhesion amount is calculated by taking the average μ of the characteristic X-ray intensity ratio as C / Fe The film adhesion amount measured by the gravimetric method when the film adhesion amount is 0 is set to 0, that is, the intercept is set to the origin, and the average μ of the film adhesion amount measured by the gravimetric method and the characteristic X-ray intensity ratio is used. C / Fe The straight line of the obtained points. In addition, the measurement of the coating adhesion amount by the weight method is obtained by using the change in the weight of the steel plate before and after the dissolution when the organic resin-coated steel plate is immersed in an alkaline solution and only the organic resin is partially dissolved, and the area of the steel plate original plate formed with the coating. The average μ of the characteristic X-ray intensity ratio C / Fe The standard deviation of the distribution of film adhesion within the same sample is measured. C / Fe The average value of all the data obtained.
[0085] When the characteristic X-ray pattern is used for evaluation, the acceleration voltage must be high enough so that incident electrons can reach the steel sheet as a substrate even in the concave portion with a large amount of film deposition and generate Fe-Kα rays of sufficient intensity. For this purpose, the measurement can be performed at an acceleration voltage of 10 kV or more.
[0086] However, if the acceleration voltage is too high, the generation efficiency of C-Kα rays decreases and the intensity decreases, so it is preferable to perform observation at 20 kV or less.
[0087] In addition, the measurement range and analysis point size of the intensity map used in this evaluation need to be measured in a manner that is statistically significant for the concavo-convex shape of the steel plate surface. In the case of a steel plate with a surface roughness of about 1 μm, the diameter of the convex portion is about 50 μm, so it is preferred that the measurement range include 200 μm×200 μm of 10 or more convex portions. In addition, the analysis point size is preferably set to 10 μm or less so that more than 10 points can be measured for each convex portion.
[0088] It should be noted that the measurement field of the intensity map may be continuous or two or more arbitrary fields of view so that the measurement range and the analysis point size satisfy the above conditions.
[0089] The relationship between the standard deviation σ of the distribution of the coating adhesion calculated as above and the friction coefficient of the coating measured separately was studied, and it was found that the standard deviation σ was less than 0.9 g / m 2 The friction coefficient becomes good.
[0090] The coating weight W per single side of the coating is preferably 2.0 g / m 2 The coating weight W per single side of the coating is greater than 2.0 g / m 2 The film adhesion amount W per single side of the film is more preferably 1.5 g / m 2 Below, particularly preferably 0.9 g / m 2 If the coating weight W per single side of the coating is 0.9 g / m 2 Below, the releasability is particularly good.
[0091] The coating adhesion amount can be determined by dividing the weight difference of the steel plate before and after coating by the area, or by completely removing the coating of the steel plate after coating with an alkaline aqueous solution or an organic solvent and dividing the weight difference of the steel plate before and after removal by the area.
[0092] The arithmetic mean roughness Ra of the steel plate base is set to 0.4 μm or more. In addition, the arithmetic mean roughness Ra of the steel plate base is preferably 2.5 μm or less.
[0093] When the arithmetic mean roughness Ra of the steel plate is less than 0.4 μm, there is a situation where fine damage that may occur during stamping is easily conspicuous, and there is a situation where the die is bitten during stamping. When the arithmetic mean roughness Ra of the steel plate is greater than 2.5 μm, there is a situation where the required coating adhesion amount becomes larger, the manufacturing cost increases, and the clarity after painting deteriorates.
[0094] The arithmetic mean roughness Ra (μm) of the steel plate can be measured according to JIS B 0633: 2001 (ISO 4288: 1996). For example, when Ra is greater than 0.1 and less than 2, the cutoff value and the reference length are set to 0.8 mm, the evaluation length is set to 4 mm, and the roughness is obtained from the measured roughness curve. When Ra is greater than 2 and less than 10, the cutoff value and the reference length are set to 2.5 mm, the evaluation length is set to 12.5 mm, and the roughness is obtained from the measured roughness curve.
[0095] Next, the method for producing the steel sheet of the present invention will be described.
[0096] The method for manufacturing a steel plate of the present invention is a method for manufacturing a steel plate having an organic resin coating containing a polyolefin wax having a melting point of 120° C. or more and an average particle size of 3.0 μm or less on the surface of a steel plate original plate. A coating in which an organic resin is dissolved or dispersed in a solvent or a coating to which wax is added is applied to the surface of a steel plate original plate and dried. Here, the coating is adjusted in such a way that the mass of the organic resin (MA) as a solid component and the mass of the wax (MB) as a solid component are set to C={MB / (MA+MB)}×100, and C is 10% by mass or more.
[0097] The mass ratio of the film components (organic resin and polyolefin wax) in the coating material is preferably 1 mass % or more and 25 mass % or less.
[0098] As a solvent for the paint, water or an organic solvent is used.
[0099] When the mass ratio of the coating component in the coating is less than 1 mass % or greater than 25 mass %, unevenness sometimes occurs during coating. The coating method is not particularly limited. As examples, methods using a roller coater, a scraper coater, and coating methods using spraying, dipping, and a brush can be cited. The drying method of the coated steel plate can be carried out by a conventional method. For example, drying using hot air, drying using an IH heater, and methods using infrared heating can be cited. The maximum temperature reached by the steel plate during drying is preferably above 60°C and below 140°C. When it is lower than 60°C, drying takes time and sometimes the rust resistance is poor. When it is higher than 140°C, the wax sometimes melts and synthesizes into one, the particle size coarsens, resulting in deterioration of lubricity, and sometimes the polymerization of the resin proceeds excessively and the demolding property decreases.
[0100] In the method for manufacturing a steel sheet of the present invention, if the result satisfies the standard deviation σ of the distribution of the coating amount is less than 0.9 g / m 2 , it is also possible to produce steel sheets with good stamping formability.
[0101] As an example of performing the coating step in operation, a coating process with σ less than 0.9 g / m 2 Adjust the coating weight W (g / m 2 ), the viscosity of the coating, and the coating conditions. Such a method for determining manufacturing conditions may be implemented as a part of the process of manufacturing the steel sheet, or may be implemented as a separate process.
[0102] Specifically, when the coating weight per single side of the coating is increased, the difference in coating weight between the convex and concave parts of the steel plate original plate becomes smaller, and the standard deviation σ of the coating weight distribution can be reduced. From this point of view, the coating weight per single side W is preferably 0.3 g / m 2 More than 0.5 g / m2 However, if the coating adhesion amount W is too much, as mentioned above, there is a case where the film release property is deteriorated, so the coating adhesion amount W per single side is preferably 2.0 g / m 2 The coating weight W per single surface is more preferably 1.5 g / m 2 Below, particularly preferably 0.9 g / m 2 In addition, when the viscosity of the coating is too low, the coating tends to accumulate in the concave parts, and the coating film thickness in the convex parts becomes thinner, and sometimes the standard deviation σ of the coating adhesion distribution becomes as low as 0.9 g / m 2 From this point of view, it is preferred to set the viscosity of the coating to 1.5 mPa·s or more. On the other hand, when the viscosity of the coating is too high, uneven coating of the coating is likely to occur, and sometimes streaky patterns are generated after the film is formed, resulting in poor appearance. Therefore, it is preferred to set the viscosity of the coating to 8.0 mPa·s or less.
[0103] In addition, when the drying time of the film becomes longer, the coating wets and spreads during the period before drying, the coating is easily accumulated in the concave part, and the liquid film thickness of the coating on the convex part becomes thinner, and sometimes the thin film area ratio of the film becomes more than 25%. Therefore, by increasing the drying temperature and shortening the drying time as much as possible within the range of satisfying the target characteristics of the film, the thin film area ratio of the film can be made less than 25%. As the drying temperature, it is preferably above 60°C, and particularly preferably above 80°C. On the other hand, as mentioned above, when the drying temperature is higher than 140°C, sometimes the wax melts and synthesizes into one, the particle size coarsens, and the lubricity deteriorates. Therefore, the drying temperature is preferably below 140°C. In addition, as the drying time, it is preferably less than 150 seconds, more preferably less than 120 seconds, and particularly preferably less than 60 seconds. However, when the drying time is too short, the coating cannot be fully dried, and sometimes the corrosion resistance is reduced. Therefore, the drying time is preferably more than 2 seconds, and particularly preferably more than 4 seconds.
[0104] As described above, by appropriately controlling the coating amount per single side of the coating, the viscosity of the coating, and the drying time of the coating, the standard deviation σ of the distribution of the coating amount can be made less than 0.9 g / m 2 .
[0105] Example
[0106] Hereinafter, the present invention will be described by way of examples. It should be noted that the present invention is not limited to the following examples.
[0107] Cold-rolled steel sheets (steel sheets No. A to C) with a thickness of 0.8 mm and arithmetic mean roughness Ra shown in Table 1 and hot-rolled steel sheets (steel sheets No. D, E, and F) with a thickness of 2.0 mm were used as steel sheet originals, and the coating material of the composition shown in Table 2 was applied by a bar coater, and dried by an IH heater in such a way that the maximum reaching temperature of the steel sheet original was 80° C., thereby obtaining steel sheets formed with a film containing an organic resin and wax. It should be noted that the steel sheet originals A to F are all SPCD or SPHD with a tensile strength of 270 MPa.
[0108]
[0109]
[0110] (1) Evaluation method of stamping formability (sliding characteristics)
[0111] In order to evaluate the press formability of the obtained steel sheet, the friction coefficient of the steel sheet was measured as follows.
[0112] Figure 4 : is a schematic front view showing a friction coefficient measuring device. As shown in the figure, a friction coefficient measuring sample 1 cut from the obtained steel plate is fixed on a sample stand 2, and the sample stand 2 is fixed on the upper surface of a horizontally movable slide 3. A slide support 5 that can move up and down and has a roller 4 in contact with the lower surface is provided on the lower surface of the slide 3, and a first force sensor 7 is installed on the slide support 5. The first force sensor 7 is used to measure the pressing load N of the blank rib 6 on the friction coefficient measuring sample 1 due to pushing up the slide support 5. A second force sensor 8 is installed at one end of the slide 3. The second force sensor 8 is used to measure the sliding resistance F of the slide 3 moving in the horizontal direction under the above-mentioned pressing force. It should be noted that the test was conducted by applying Preton (registered trademark) R352L, a stamping cleaning oil manufactured by Sugimura Chemical Industry Co., Ltd., as a lubricating oil, to the surface of the sample 1.
[0113] Figure 5 1 is a schematic perspective view showing the shape and size of the bead used. The bead 6 slides with its lower surface pressed against the surface of the sample 1. Figure 5 The shape of the blank holder 6 shown is that the width is 10mm and the length in the sliding direction of the sample is 59mm. The lower part at both ends of the sliding direction is composed of a curved surface with a curvature of 4.5mmR. The lower surface of the blank holder rib that presses the sample has a plane with a width of 10mm and a length of 50mm in the sliding direction.
[0114] For the friction coefficient measurement test, use Figure 5The blank holder shown was carried out with the pressing load N set to 400 kgf and the sample pulling speed (horizontal moving speed of the slide 3) set to 20 cm / min. The friction coefficient μ between the test material and the blank holder was calculated by the formula: μ=F / N.
[0115] When the friction coefficient was 0.119 or less, the sliding property was considered to be particularly good and was evaluated as ◎. When the friction coefficient was greater than 0.119 and less than 0.130, the sliding property was considered to be good and was evaluated as 0. When the friction coefficient was greater than 0.130, the sliding property was considered to be insufficient and was evaluated as ×.
[0116] (2) Evaluation method of film release properties
[0117] Assuming that the steel plate of the present invention is used for automotive purposes, the removability of the steel plate during degreasing was evaluated. In order to determine the removability of the steel plate, first, each test piece cut from the obtained steel plate was degreased using Fine Cleaner (registered trademark) E6403 (manufactured by Japan Parkersei Co., Ltd.) as an alkaline degreasing agent. For this treatment, the test piece was immersed in a degreasing liquid with a degreasing agent concentration of 20 g / L and a temperature of 40°C for a prescribed time and washed with tap water. For the test piece after this treatment, the surface carbon intensity was measured using a fluorescent X-ray analyzer, and the film peeling rate was calculated according to the following formula using the measured value and the previously measured surface carbon intensity before degreasing and the measured value of the surface carbon intensity of the untreated steel plate.
[0118] Film peeling rate (%) = [(carbon strength before degreasing - carbon strength after degreasing) / (carbon strength before degreasing - carbon strength of untreated steel plate)] × 100
[0119] The film releasability of the steel sheet was evaluated according to the following criteria based on the immersion time in the alkaline degreasing solution with a film peeling rate of 98% or more. In the case of ◎, ○, and △ below, the film releasability was judged to be acceptable.
[0120] ◎(Particularly good): within 15 seconds
[0121] ○ (Good): More than 15 seconds and less than 45 seconds
[0122] △(Qualified): more than 45 seconds and less than 120 seconds
[0123] ×(bad): more than 120 seconds
[0124] (3) Evaluation method of standard deviation σ of film adhesion amount
[0125] The standard deviation σ of the coating adhesion amount of the obtained steel sheet was measured as follows.
[0126] Five 10 mm square pieces were cut from the steel plate obtained above to prepare test materials. A Schottky field emission SEM (Σigma manufactured by Carl Zeiss) equipped with an energy dispersive X-ray spectrometer (XFlash5|30 manufactured by Bruker) was used for the measurement.
[0127] For each level of steel plate, the intensity diagrams of C-Kα and Fe-Kα rays were measured at a magnification of 300 times from the center of each of the five test materials under the conditions of an accelerating voltage of 15 kV and a measurement point number of 800 points × 600 points. The measured C Kα ray intensity diagram was divided by the corresponding Fe-Kα ray intensity diagram to calculate the C-Kα / Fe-Kα intensity ratio diagram. Furthermore, the average value μ of the C-Kα / Fe-Kα intensity ratio was calculated from the intensity ratio diagram. C / Fe and standard deviation σ C / Fe , the average value of the five viewing fields is used for evaluation. C / Fe The relationship between the amount of film adhesion and the standard deviation of the C-Kα / Fe-Kα intensity ratio σ C / Fe The standard deviation σ of the coating adhesion amount was converted. The σ obtained above is less than 0.9 g / m 2 The evaluation was good (○) when σ was 0.9 g / m 2 The above cases were evaluated as poor (×).
[0128]
[0129]
[0130]
[0131] According to Tables 3 to 5, the steel sheets of the examples of the present invention all have excellent stamping formability. In contrast, the steel sheets of the comparative examples that do not have the technical features of the present invention all have poor stamping formability. In addition, by setting the mass ratio of wax in the film to less than 50 mass % and setting the amount of adhesion per single side of the film to 2.0 g / m 2 Hereinafter, excellent demolding properties were obtained.
[0132] Industrial Applicability
[0133] The steel sheet of the present invention is excellent in press formability and mold release properties and can be used in a wide range of fields, mainly for automobile bodies.
[0134] Explanation of symbols
[0135] 1. Sample for determination of friction coefficient
[0136] 2. Sample table
[0137] 3 slides
[0138] 4 Rollers
[0139] 5 Slide support platform
[0140] 6 Edge ribs
[0141] 7First force sensor
[0142] 8 Second force sensor
[0143] 9 rails
Claims
1. A steel plate comprising a steel plate base plate and a coating formed on at least one surface of the steel plate base plate, wherein: The film comprises an organic resin and wax, The arithmetic mean roughness Ra of the steel plate is greater than 0.4 μm, The organic resin is at least one of acrylic resin, epoxy resin, urethane resin, phenolic resin, vinyl acetate resin, and polyester resin. The wax is a polyolefin wax having a melting point of 120° C. or higher and 140° C. or lower and an average particle size of 3.0 μm or lower, The proportion of the wax in the film is 10% by mass or more, The standard deviation σ of the distribution of the coating amount per single side of the coating is less than 0.9 g / m 2 .
2. The steel plate according to claim 1, wherein: The coating weight W per single side of the coating is 2.0 g / m 2 the following.
3. The steel plate according to claim 1 or 2, wherein: The steel sheet base has an arithmetic mean roughness Ra of 0.4 μm or more and 2.5 μm or less.
4. The steel plate according to any one of claims 1 to 3, wherein The wax has an average particle size of 0.01 μm or more and 0.5 μm or less.
5. The steel plate according to any one of claims 1 to 4, wherein The ratio of the wax in the film is less than 50% by mass.
6. The steel plate according to any one of claims 2 to 5, wherein The coating weight W per single side of the coating is 0.9 g / m 2 the following.
7. The steel plate according to any one of claims 1 to 6, wherein The organic resin is an alkali-soluble resin.
8. A method for producing a steel plate, which is the method for producing a steel plate according to any one of claims 1 to 7, wherein: A coating material containing the organic resin according to any one of claims 1 to 7 and a wax is applied to at least one surface of a steel plate original sheet and dried.
9. The method for manufacturing a steel plate according to claim 8, wherein: The coating has a viscosity of 1.5 mPa·s or more and 8.0 mPa·s or less.
10. The method for manufacturing a steel plate according to claim 8 or 9, wherein: The maximum reaching temperature of the steel plate original plate during the drying is 60° C. or higher and 140° C. or lower, and the drying time during the drying is 2 seconds or higher and 150 seconds or lower.
Citation Information
Patent Citations
Resin coated metal plate with mold drag resistance and corrosion resistance and its manufacture
JP1998052881A
Alkali-soluble type organic film-coated steel sheet having excellent adhesiveness and anti-mold galling property
JP2000167981A
Coating composition having ability to form lubricative film excellent in press-moldability and scuffing- resistance, and of alkali-soluble type, and metal product having lubricatively treated surface using this composition
JP2000309747A
Steel sheet having lubricating film and production method therefor
CN112513330A
Resin coated composite steel plate excellent in after-processing appearance
JP1993077357A
